A Cost Benefit Analysis from Instructor, Community Partner, and Student Perspectives: Cabrini College CBR Courses Merge Service, Education, and Research - David Dunbar; Caroline Nielsen; Nancy Watterson; Janice Xu; Melissa Terlecki; Jenna Cardone; Lisa Ratmansky; Christina Medved; Susan Gill; Owen Owens (The University of Alabama, 2022)
Two community-based research (CBR) courses-Watershed Citizenship and Watershed Ecology-were piloted at Cabrini College in southeastern Pennsylvania. The courses connected service, education, and research using a local Pennsylvania stream, Crabby Creek, as the focal point, while working with several community partners. Course feedback using a qualitative student focus group regarding attitudes about environmental awareness, interdisciplinary thinking, and community-based, undergraduate research experiences showed that students gained a better understanding of how different disciplines can collaborate to address a problem in an integrative manner. Students also valued the faculty interdisciplinary team-teaching approach of the courses. We offer a model for designing and conducting an interdisciplinary team-taught CBR course employing instructors with different disciplinary backgrounds and areas of expertise. In this paper we present a case study in which we discuss the benefits and costs of these types of courses offered through the eyes of course instructors, community partners, and students and emphasize lessons learned that should prove helpful for others considering developing similar courses.